2015
DOI: 10.1055/s-0035-1557898
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor-Mediated Upregulation of CYP3A4 and MDR1 by Quercetin in Caco-2 cells

Abstract: To examine whether quercetin interacts with vitamin D receptor, we investigated the effects of quercetin on vitamin D receptor activity in human intestinal Caco-2 cells. The effects of quercetin on the expression of the vitamin D receptor target genes, vitamin D3 24-hydroxylase, cytochrome P450 3A4, multidrug resistance protein 1, and transient receptor potential vanilloid type 6 were measured using quantitative polymerase chain reaction. The vitamin D receptor siRNA was used to assess the involvement of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
(69 reference statements)
2
5
0
Order By: Relevance
“…In this study, Caco-2 cell line was firstly selected as an in vitro model for validating the effects of quercetin on P-gp expression at the transcriptional and translational level. These results established that quercetin is a potential inducer of P-gp mRNA/protein, which was consistent with some previous reports about flavonoids inducing the P-gp expression 15 , 24 , 25 . Therefore, the in vivo tests in chicken were undertaken.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, Caco-2 cell line was firstly selected as an in vitro model for validating the effects of quercetin on P-gp expression at the transcriptional and translational level. These results established that quercetin is a potential inducer of P-gp mRNA/protein, which was consistent with some previous reports about flavonoids inducing the P-gp expression 15 , 24 , 25 . Therefore, the in vivo tests in chicken were undertaken.…”
Section: Discussionsupporting
confidence: 93%
“…It is reported that various flavonoids including quercetin regulated the P-gp expression through pregnane X receptor (PXR) and constitutive androstane receptor (CAR) 32 in human, and recently, it is also reported that quercetin upregulated the P-gp through vitamin D receptor (VDR) dependent pathway in Caco-2 cells 25 . It was previously demonstrated that the quercetin has potential to interact with multiple targets via judicious analysis using reverse docking methods 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of VDR siRNA suggested that the effects of quercetin on CYP3A4 required the normal functions of VDR in Caco-2 cells. Other quercetin-like flavonoids (kaempferol and berberine) of equal concentration and treatment duration resulted in similar effects on these genes 93 . The inductive effects of complementary and alternative medicines (CAM) on CYP3A4 through PXR- or CAR-mediated pathway has been elucidated 94 .…”
Section: Regulatory Roles Of Vdr On Cyp3a In Different Speciesmentioning
confidence: 99%
“… 27 Another in vitro study on Caco-2 cells confirmed that three consecutive days of KMF and Quercetin treatment could induce a considerable increase in the mRNA expression for both P-gp and CYP3A4. 28 …”
Section: Discussionmentioning
confidence: 99%